Pola penggunaan obat anti diabetes mellitus tipe-II pada pasien rawat inap di RSUD Praya tahun 2021 - Novita, Adela; Hasina, Raisya; Harahap, Herpan Syafii (Universitas Mataram, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion. The prevalence of people with diabetes mellitus in Indonesia reached 6.2% per year in 2020 and ranks 7th in the world with 8.5 million people. Based on the results of observations at the Praya Hospital in 2021, type-II diabetes mellitus is the 4th highest-order disease suffered by the community, especially Central Lombok Regency, with a total incidence of 131 patients. This study aims to determine the pattern of drug use and HbA1c profile in patients with type-II diabetes mellitus in the inpatient installation of Praya Hospital in 2021. This study was retrospective, using the Nonprobability Sampling method, namely the type of purposive sampling so that a sample of 96 medical records of diabetes mellitus patients was obtained type-II. The data is presented as pie charts and tables in percentages, which were analyzed using Microsoft Excel and SPSS version 25. From the results of this research, it was found that the pattern of drug use at Praya Hospital in 2021 was given the highest from each group namely the oral antidiabetic drug group (OAD) was in the Biguanid class with 61 drugs (8,13%), while insulin drugs were in the Rapid-Acting class with 343 drugs (45,73%), and the OAD + Insulin combination with 119 drugs (15,87%). For the HbA1c profile, high HbA1c levels were found in 76 patients (79%). This shows that blood glucose control is not reasonable. Based on the study's results, the recommended recommendation is that patients routinely control blood sugar and be educated on the accuracy of drug use to control blood sugar.